Research on Adaptation of First-Year Students with Special Educational Needs to Study at University - Moldakhanova , Marzhan; Kariyev , Adlet; Lekerova , Gulsim; Orazbayeva , Fauziya (Insight: the psychological dimensions of society, 2024)
The aim of the research is empirical clarification and theoretical substantiation of psychological adaptive potential and types of adaptation of first-year students with special educational needs in terms of university education. First-year students of M. Auezov South Kazakhstan University (SKU named after M. Auezov) and Abai Kazakh National Pedagogical University (KNPU named after Abai) took part in the research, a total of 469 people in the age range from 17 to 19 years. First-year students with special educational needs numbered 154 people. Descriptive frequency characteristics of the sample: M=18.22; SD=±2.45; Me=18.00; Mo=18.00. Methods. Valid and reliable questionnaires were used: the test of personality adjustment (TPA) (Rogers & Dymond, 1955); the multilevel personal questionnaire “Adaptability” (MPQ-AM) (Maklakov & Chermyanin, 1993). Inductive and deductive methods, analysis, generalization, substantiation and synthesis of scientific theoretical and empirical data were used. Results. It was found that according to the “adaptability” scales (U=245.00; p=.000); “self-acceptance” (U=312.00; p=.003); “acceptance of others” (U=318.00; p=.004); “behavioral regulation” (U=241.00; p=.000); “communicative potential” (U=203.00; p=.000) and “personal adaptation potential” (U=312.00; p=.003) first-year students with special educational needs are inferior to students without special educational needs. Such expected results were explained by certain difficulties in the process of communication, including representatives of the opposite sex. The absence of statistical significance between the respondents with special educational needs (Group 1) and those without special educational needs (Group 2) according to the parameter “moral normativity” (U=621.00; p=.059) was established. It was explained that the key value of this contingent of first-year students is the constancy of formed moral canons. Using k-means clustering, four types of adaptation of firstyear students with special educational needs to study at university were determined: “Constructive adaptation” (cluster 1, n=20; 12.99%), “Destructive adaptation” (cluster 2, n=57; 37.01%), “Maladjustment” (cluster 3, n=49; 31.82%), “Moral-normative adaptation” (cluster 4, n=28; 18.18%). The obtained types organize a significant array of empirical information about the special educational needs of students for the purpose of further operationalization and effective implementation in educational practice. Discussion and conclusions. We proved the possibility of introducing the research results in terms of improvement of the inclusive educational environment for optimal adaptation of first-year students to the realities of university life for the purpose of fulfillment of expectations of all subjects of educational process.